Towards an international comparative history of vocational education and training : Editorial - Gonon, Philipp [Verfasser]; Deissinger, Thomas [Verfasser] (My University, 2021)
"The aim of the articles in this issue is to offer answers to the question about why VET systems developed as they did. So, we can say that the trajectory of VET systems is always embedded within a narrative of gradual change. Some would call this evolution or even modernisation. In any case, VET in its modern form, which includes schools and with them a public and political dimension, was established and developed under the shaping influence of the respective cultural, political and socio-economic national conditions of individual countries." (Text excerpt ; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S System beruflicher Bildung; S 2.3 Berufsbildungspolitik; 370; Berufsausbildung; Berufsbildungssystem; Historische Entwicklung; Berufsbildungspolitik; Einflussfaktor